La cinética de la esterificación de ácidos carboxílocos es de segundo orden con repecto al alcohol - Arias Carrillo, Maynor (Universidad de Costa Rica, 2009)
Esterification of carboxylic acids with alcohols is considered as AAC2 type reaction. The specific rate of esterification of acetic acid with methanol, in mixtures of acetonitrile-methanol showed a quadratic dependence on the alcohol concentration. This second order dependence suggests a general base catalyzed mechanism analogous to the [H2O]2 kinetic dependence observed in the acidcatalyzed hydrolysis of carboxylic esters, in highly aqueous media.